Seychelles : First Review Under the Extended Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
Program implementation and economic fundamentals continue to be strong, but the external position weakened in mid-2014. Projected growth for 2014 has been revised down to 2.8 percent from 3.7 percent, due to weaker demand for Seychelles' two main exports-tourism and canned tuna. At the same time, strong growth in personal earnings and private sector credit have fueled a surge in imports, putting further pressure on the balance of payments. As a result, the exchange rate depreciated an estimated 11 percent in nominal effective terms from early August to late-October.